2009
DOI: 10.1002/qsar.200710073
|View full text |Cite
|
Sign up to set email alerts
|

QSPR Study on the Melting Points of a Diverse Set of Potential Ionic Liquids by Projection Pursuit Regression

Abstract: A Quantitative Structure -Property Relationship (QSPR) study was carried out to model the melting points for a diverse set of 288 potential Ionic Liquids (ILs) including pyridinium bromides, imidazolium bromides, benzimidazolium bromides, and 1-substituted 4-amino-1,2,4-triazolium bromides. Based on the calculated descriptors by CODESSA program, a Principal Component Analysis (PCA) was performed on the whole data to detect the homogeneities in the dataset and to assist the separation of the data into represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…According to the authors, the most significant descriptors were, the indices reflecting the coordination ability of the cation, the average nucleophilic reactivity index for the N atom related to electrostatic intermolecular interactions and the total entropy per atom related to the difference in conformational and rotational degrees of freedom in solid and liquid phases. Many other models [22][23][24][25][26][27][28][29] have been developed for several families of ILs (Table 2), most of them for imidazoliumbased ILs with the same anion; consequently, their range of application is quite limited.…”
Section: Qspr Methodsmentioning
confidence: 99%
“…According to the authors, the most significant descriptors were, the indices reflecting the coordination ability of the cation, the average nucleophilic reactivity index for the N atom related to electrostatic intermolecular interactions and the total entropy per atom related to the difference in conformational and rotational degrees of freedom in solid and liquid phases. Many other models [22][23][24][25][26][27][28][29] have been developed for several families of ILs (Table 2), most of them for imidazoliumbased ILs with the same anion; consequently, their range of application is quite limited.…”
Section: Qspr Methodsmentioning
confidence: 99%
“…Another correlation for various families of bromide ILs (including pyridinium, imidazolium, benzimidazolium, and 1-substituted 4-amino-1,2,4-triazolium) was proposed by Ren et al 172 Using the CODESSA descriptors and a PCA analysis, the best correlation reported (an eight-descriptor non linear model) has R 2 = 0.804 and an AARD (%) of 18. 39 174 Here the authors used multiple approaches to perform QSPR modelling of the melting point of a structurally diverse data set of 717 bromides of nitrogencontaining organic cations.…”
Section: Melting Pointsmentioning
confidence: 99%
“…Amongst them, Duplex seems to be the best way to select representative training and test sets in a validation context and its principle as well as the treating procedure are described in literature 34 . In addition to above approaches, PCA was another very useful method proved by our previous works to assist the data splitting 35,36 . Design of the training set is performed with respect to the PCs by selecting a subset of substances that are most efficient in spanning the substance (or PCA model) space.…”
Section: Resultsmentioning
confidence: 99%